An integrated mechanism of G q regulation of PLCβ enzymes - Kanishka Senarath; Isaac J. Fisher; Wonjo Jang; Sumin Lu; Asuka Inoue; Evi Kostenis; Angeline M. Lyon; Nevin A. Lambert (Proceedings of the National Academy of Sciences, 2025)
Phospholipase Cβ (PLCβ) enzymes are the principal effectors activated by G q heterotrimers. Both Gα q and Gβγ subunits can activate PLCβ, which requires precise positioning of PLCβ at the plasma membrane to relieve structural autoinhibition and give the active site access to the phosphatidylinositol 4,5-bisphosphate (PIP2) substrate. PLCβ enzymes possess a unique distal C-terminal domain (dCTD) that is critical for activation by Gα q , but the reason for this is unclear. It is also not known how G protein activation affects the subcellular localization of PLCβ enzymes, some of which are found primarily in the cytosol despite needing to act at the plasma membrane. Here, we use bioluminescence spectroscopy, imaging, and gene editing to study the membrane disposition of PLCβ enzymes in living cells and to define the functional roles of the dCTD. We find that PLCβ translocates to the plasma membrane upon G q activation, primarily by binding to Gα q subunits. This is rapidly counteracted by PIP2 hydrolysis, which promotes PLCβ translocation back into the cytosol. PLCβ translocation and activation require binding of Gα q to the catalytic domain and the dCTD at two distinct interfaces. Gα q binding to the dCTD is required for activation even when PLCβ is artificially tethered to the plasma membrane, suggesting that this domain has functions beyond simply recruiting the enzyme to the PIP2 substrate. We propose that in addition to associating PLCβ with the plasma membrane, the dCTD reorders the αN helix of active Gα q and thus participates directly in the precise positioning of the catalytic domain.